2006
DOI: 10.1089/vbz.2006.6.423
|View full text |Cite
|
Sign up to set email alerts
|

Serologic Evidence for Exposure toRickettsia rickettsiiin Eastern Arizona and Recent Emergence of Rocky Mountain Spotted Fever in This Region

Abstract: During 2002 through 2004, 15 patients with RockyMountain spotted fever (RMSF) were identified in a rural community in Arizona where the disease had not been previously reported. The outbreak was associated with Rickettsia rickettsii in an unexpected tick vector, the brown dog tick (Rhipicephalus sanguineus), which had not been previously associated with RMSF transmission in the United States. We investigated the extent of exposure to R. rickettsii in the local area through serologic evaluations of children and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
42
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 19 publications
1
42
2
Order By: Relevance
“…Harrus et al (2007) revealed higher seroprevalence rates among dogs in endemic zones where human disease have been reported. Also studies by Segura Porta et al (1998) and Demma et al (2006) found that canine rickettsioses often precede outbreaks in human populations. Thus, further serological studies on dog population in other provinces should be carried out to identify the possible endemic areas of rickettisioses within the country.…”
Section: Discussionmentioning
confidence: 94%
“…Harrus et al (2007) revealed higher seroprevalence rates among dogs in endemic zones where human disease have been reported. Also studies by Segura Porta et al (1998) and Demma et al (2006) found that canine rickettsioses often precede outbreaks in human populations. Thus, further serological studies on dog population in other provinces should be carried out to identify the possible endemic areas of rickettisioses within the country.…”
Section: Discussionmentioning
confidence: 94%
“…Spotted fever group rickettsioses are emerging worldwide (Parola et al 2005, Jones et al 2008. For example, a cluster of 16 human cases of Rocky Mountain spotted fever in Arizona was associated with an epidemic in dogs and infestation of the brown dog tick, Rhipicephalus sanguineus (Demma et al 2006). In Humboldt County, bears would likely be exposed to rickettsiae via Dermacentor spp.…”
Section: Discussionmentioning
confidence: 99%
“…14,25 The seasonal variation in RMSF cases from this region may be caused by a different disease ecology in the Southwest. 14,35,36 Specifically, Rh. sanguineus , the tick responsible for transmission in this region, may have a different cycle of peak tick activity.…”
Section: Discussionmentioning
confidence: 99%